Tailoring compressive strength and absorption energy of lightweight multi-phase alcusifex (X = cr, mn, zn, sn) high-entropy alloys processed via powder metallurgy - Sharma, Ashutosh; Lee, Hansung; Ahn, Byungmin (Materials, 2021)
The development of lightweight HEAs with high strength and low cost is an urgent re-quirement. In this study, equimolar AlCuSiFeX (X = Cr, Mn, Zn, Sn) lightweight HEAs were fabricated by advanced powder metallurgy. The mechanical alloying was performed for 45 h, and the powder compacts were densified at 650 °C. The final results revealed that AlCuSiFeSn lightweight HEA was composed of a single face-centered cubic (FCC) and Cu81Sn22, whereas AlCuSiFeZn showed a dual FCC and body-centered cubic (BCC) structures. Similarly, AlCuSiFeMn alloy con-tained a BCC + FCC phase with a µ-phase, whereas a σ-phase was present in AlCuSiFeCr in addition to FCC + BCC phases. We also calculated various thermodynamic parameters to predict the solid-solution phase stability of each of the above lightweight HEAs. It was found that lightweight HEAs with additive elements Sn and Zn tend to predominant FCC phases, whereas those with Cr and Mn result in major BCC with hard µ and σ phases, which further improve their mechanical strength. A maximum fracture strain of 23% was obtained for AlCuSiFeSn followed by 19% for AlCuSiFeZn HEA. The compressive fracture mechanisms of these lightweight HEAs are also discussed and re-ported here.
Keywords: Absorption energies; Additive elements; Body-centered cubic (bcc) structure; Compressive fracture; Face-centered cubic; Fracture strain; Solid solution phase; Thermodynamic parameter; Absorption energy; High entropy alloy; Lightweight; Powder metallurgy; Thermodynamics